Communication in Venados (2017)
A group of researchers went to Venados, a verge of the Las Orquídeas National Park, to explore the mammals of that park, where they had the opportunity to exchange knowledge with jealous settlers who are peasants and indigenous katío and obtained some apprenticeships for field work.